Impact of fermented foods consumption on gastrointestinal wellbeing in healthy adults: a systematic review and meta-analysis - Mukherjee, Arghya; Farsi, Dominic N.; Garcia-Gutierrez, Enriqueta; Akan, Ecem; Millan, Jose Angel Salas; Angelovski, Ljupco; Bintsis, Thomas; Gérard, Amaury; Güley, Ziba; Kabakcı, Sümeyye; Kahala, Minna; Merabti, Ryma; et al. (Frontiers in Nutrition, 2025)
ObjectiveIn recent years, the consumption of fermented foods (FFs) has been linked with gastrointestinal health and wellbeing. Here, we systematically review and meta-analyse the currently available evidence relating to this as part of the COST Action PIMENTO and guided by the European Food Safety Authority (EFSA) health claim dossiers.MethodsMEDLINE, Scopus and Cochrane CENTRAL bibliographic libraries were searched for relevant literature up to 31st January 2025. All eligible studies were included for narrative review as per EFSA guidelines, but only randomised controlled trials (RCTs) were considered for meta-analyses. Risk of bias, mechanisms of action, bioactive compounds and safety were additionally discussed. Data was pooled using mean difference (MD)/standardized MD for continuous data and relative risk (RR) for dichotomous data. Certainty of evidence was evaluated through GRADE assessment.ResultsA total of 25 studies (19 RCTs included in meta-analysis) with 4,328 participants were included in the systematic review. Meta-analysis demonstrated the beneficial impact of FF consumption on frequency of bowel movements (MD 0.60, CI 0.04, 1.16, p = 0.04, I2 = 74%), stool consistency (Bristol Stool Form Scale) (MD 0.25, CI 0.03, 0.47, p = 0.03, I2 = 72%), gastrointestinal symptoms (SMD −0.60, CI −1.05, −0.15, p = 0.009, I2 = 90%) and intestinal transit time (−13.65 CI −21.88, −5.43, p = 0.001, I2 = 95%), among others. Certainty of evidence was highly variable and mostly low.ConclusionOur analysis suggests that FF consumption beneficially impacts the frequency of bowel movements, stool consistency, incidence of hard stools, intestinal transit time, abdominal symptoms, bloating, borborygmi, flatulence and degree of constipation.Systematic review registrationThis study was registered at the Open Science Framework (osf.io, registration number: q8yzd).